2008
DOI: 10.1007/s10461-008-9441-x
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Other Psychosocial Factors as Predictors of Adherence to Highly Active Antiretroviral Therapy (HAART) in Adults with Comorbid HIV/AIDS, Psychiatric and Substance-related Disorder

Abstract: This study assessed adherence to HAART among 67 HIV-infected adults, and the degree to which gender and psychological factors-including depression, drug and alcohol use, quality of life, and medication side effects-influenced adherence. Although overall adherence was greater than rates reported in similar studies, no significant difference in adherence was observed between men and women in the present sample. Medication side effects were a significant predictor of non-adherence in the sample at large and among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 12 publications
(17 reference statements)
6
34
0
2
Order By: Relevance
“…Contudo, o estudo de Applebaum et al 36 trabalhou com uma amostra muito reduzida, de forma que os resultados não podem ser generalizados para outras populações, e no estudo de Lazo a amostra de indivíduos do gênero masculino foi retirada de uma coorte realizada em quatro cidades americanas, incluindo apenas indivíduos MSM (men who have sex with men). Dessa forma, conclusões sobre o gênero e adesão também não podem ser estendidas para a população geral de pessoas com AIDS 36,37 .…”
Section: Discussionunclassified
“…Contudo, o estudo de Applebaum et al 36 trabalhou com uma amostra muito reduzida, de forma que os resultados não podem ser generalizados para outras populações, e no estudo de Lazo a amostra de indivíduos do gênero masculino foi retirada de uma coorte realizada em quatro cidades americanas, incluindo apenas indivíduos MSM (men who have sex with men). Dessa forma, conclusões sobre o gênero e adesão também não podem ser estendidas para a população geral de pessoas com AIDS 36,37 .…”
Section: Discussionunclassified
“…Similarly, self-report of three or more adverse reactions were associated with an increased risk of non-adherence [41]. Likewise, medication side effects were a significant predictor of nonadherence in the sample at large and among women in particular [42]. Study done in Brazil in 2015 showed that adverse drug reaction was associated with non-adherence [43].…”
Section: Side Effects Of Antiretroviral Drugs and Non-adherencementioning
confidence: 99%
“…Pequeños incumplimientos de esta adherencia, se asocian a fracaso terapéutico (pérdida de la capacidad de suprimir la replicación viral con la consiguiente progresión de la enfermedad), agravado por la pérdida de efectividad de los anti-retrovirales previamente usados (desarrollo de resistencia) 29,[34][35][36] . Entre los factores psico-sociales más importantes para la pérdida de adherencia están: la falta de una red de apoyo social, el abuso de sustancias y la depresión 23,28,29,[34][35][36][37][38][39] . Se considera que la depresión no tratada es, a su vez, un factor de riesgo para el abuso de sustancias y el uso de terapias alternativas o la automedicación, con el subsecuente perjuicio en la adherencia y efectividad de la TAR 4,11,18,28,31,32 .…”
Section: Factores Asociadosunclassified